2019
DOI: 10.3389/fgene.2019.00827
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Genome-Wide Association Studies With Pathway Analysis and Gene Expression Analysis Highlights Novel Osteoarthritis Risk Pathways and Genes

Abstract: Osteoarthritis (OA) is the most common degenerative joint disorder worldwide. To identify more genetic signals, genome-wide association study (GWAS) has been widely used and elucidated some OA susceptibility genes. However, these susceptibility genes could only explain only a small part of heritability of OA. It is suggested that the identification of disease-related pathways may contribute to understand the genomic etiology of OA. Here, we integrated the GWAS into pathway analysis to identify novel OA risk pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…miRSNPs have functional consequences for autoimmune diseases including MS [ 31 ]. Statistical approaches and meta-analysis of neurological diseases A recent study showed that miRSNPs have an expression quantitative trait locus (eQTL) effect on genes reported in GWAS [ 33 ], and the number of miRSNPs associated with human diseases keep increasing [ 34 , 35 ]; A recent study integrated GWAS with pathways to report novel risk pathways and genes [ 36 ]. We believe that the existing analysis on MS cognitive dysfunction can reveal the pathways and genes with common risks that are associated with the cognitive dysfunction in MS.…”
Section: Introductionmentioning
confidence: 99%
“…miRSNPs have functional consequences for autoimmune diseases including MS [ 31 ]. Statistical approaches and meta-analysis of neurological diseases A recent study showed that miRSNPs have an expression quantitative trait locus (eQTL) effect on genes reported in GWAS [ 33 ], and the number of miRSNPs associated with human diseases keep increasing [ 34 , 35 ]; A recent study integrated GWAS with pathways to report novel risk pathways and genes [ 36 ]. We believe that the existing analysis on MS cognitive dysfunction can reveal the pathways and genes with common risks that are associated with the cognitive dysfunction in MS.…”
Section: Introductionmentioning
confidence: 99%